The Analysis The Financial Perfomance Using Financial Ratio By The Decree Of The Indonesian Minister For Soe - Nur Sabila Soraya Amalina; Hadiahti Utami; Noor Suroija (Universitas Muhammadiyah Prof. DR HAMKA., 2020)
This research is aimed at investigating the financial performance of Indonesian Port Corporation III (Persero) of Tanjung Emas Semarang Branch in the period of 2005-2014. The analysis to assess the financial aspects of the company is based on the Decree by The Minister for State-owned Enterprises Number: KEP-100/MBU/2002. The financial aspects are evaluated by seven indicators, namely: Return on Equity (ROE), Return on Investment (ROI), cash ratio, current ratio, collection periods, total assets turnover, total equity to total assets. In the period of 2005 to 2011, the company had always been attaining the sound grade in A category. However, from 2012 to 2014, the performances of the company have been descending to the grade of the BBB category.